The Effect Application of Cooperative Learning Model STAD Type of Students Learning Outcomes on Atomic Structure Material at Class X of SMAN 4 Sigi - Mariani, Sri; Said, Irwan; Ratman, Ratman (Universitas Tadulako, 2019)
The purpose of this research is to determine the effect of application of cooperative learning model STAD type (student-Teams-Achievement-Division) to high school in Â Sigi. Type of the research was quasi experiment with non-randomized pretest-posttest control group design. The reseach population was all students of class X with sampilng technique was purposive sampilng method. Sample used for testing of students learning outcomes data used two-partiest-test statistic analysis. The result of data analysis obtained the average value(X1) experiment class was 66.17 with a standard deviation of 13.18. The results of hypothesis testing with two-parties t- test statistic were obtaied â€“ttable,<tcount>+ttable ( tcount= 7.04 and ttable = 2.02) with signifance level Î± = 0.05 and degrees of freedom was 42, so H0 was rejected and Ha was accepted. Therefore, it can be concluded that there is an effect of the application of cooporative learning model STAD type to the studentâ€™s learning outcomes on atomic structure material at class X of SMAN 4 Sigi.